Elderly monitoring system - Wang, Guo Wei (Nanyang Technological University, 2020)
With the rise of aging population in Singapore, the number of elderlies living alone has also increased. To allow caretakers to monitor the health of the elderlies, an affordable Elderly Monitoring System is needed. Hardware that are affordable together with a system were deployed to test for effectiveness. An affordable Bluetooth LE wrist tracker is given to the elderly for monitoring purpose. The tracker data are collected and sent to the system regularly. The deployed system provides features that allows caretakers to monitor the elderly from anywhere with internet access. This means caretakers can work during the day without worry and will even be informed for emergencies through SMS. Through testing, it was found out that hardware failure may occur during monitoring, and some features may not give accurate results. It was concluded that more test needs to be conducted and with the collected data, improve the algorithms used for the features.